Personal Innovativeness and Perceived System Quality for Information System Success: the Role of Diffusability of Innovation - Donmez-Turan, Aygul; Zehir, Cemal (UNIV OSIJEK, TECH FAC, 2021)
In the present study, the researchers aim to explain diffusion of innovation on the basis of technology acceptance as well as adaptation to information technology innovation, and put forward the relationships with perceived system quality and personal innovativeness as its antecedents and system usage as its consequence for information system success. Following previous studies, electronic document management systems' diffusability and employing such systems are the subject of this research. Having gathered the data from 262 administrative personnel working at a state university, we first conducted explanatory and confirmatory factor analyses on each scale, then constructed the measurement model and structural model. Results indicated that diffusability of innovation partially mediated the relationship between personal innovativeness and information system success measured by system usage. In addition, diffusability of innovation fully mediated the relationship between perceived system quality and information system success. Present research has been designed to explain management information system success with individual and system related factors, personal innovativeness and system quality, respectively. In addition, as a reflective construct diffusability of innovation has been defined on the basis of formative construct of diffusion of innovation and all its dimensions have been examined as a single latent construct, unlike the previous researches.
Keywords: diffusability of innovation; diffusion of innovation; information system success; perceived system quality; personal innovativeness; system usage; technology acceptance model; USER ACCEPTANCE; MCLEAN MODEL; USAGE INTENTION; ADOPTION; TECHNOLOGY; SERVICES; PERCEPTIONS; DELONE; Engineering